Evaluating English Teachers’ Perception of Community Language Learning in Enhancing Speaking Confidence - Hadi Jaza, Zimam Farid; Uctuvia, Vina; Salam, Badrus (Institut Agama Islam Negeri (IAIN) Manado, 2024)
Building self-confidence in speaking is a fundamental challenge in English language learning, particularly in non-native settings. Many students experience anxiety and hesitation when asked to speak in a second language, making it essential to adopt supportive teaching approaches. Addressing this issue requires innovative and student-centered teaching methods that foster a positive and engaging learning atmosphere. This study examines English teachers' perceptions of Community Language Learning (CLL) in enhancing students' self-confidence in speaking classes. Adopting a qualitative research design, the study involved interviews with four experienced English teachers at SMP 2 Boja, who shared their insights and classroom experiences. The findings indicate that CLL creates a supportive, low-pressure classroom environment that helps reduce language anxiety and encourages active student participation. Teachers emphasized the importance of the teacher's supportive role, the use of group interactions, and the collaborative nature of CLL in boosting students' speaking confidence. The study concludes that CLL is an effective method for improving students' self-confidence in speaking activities, highlighting its potential for broader application in similar educational contextsKeywords: Community Language Learning (CLL), English Speaking Confidence, Teacher Perceptions